2010
DOI: 10.1136/gut.2010.210732
|View full text |Cite
|
Sign up to set email alerts
|

Association of the G-protein and  2-adrenergic receptor gene and plasma norepinephrine level with clonidine improvement of the effects of diuretics in patients with cirrhosis with refractory ascites: a randomised clinical trial

Abstract: These results suggest that neurohormonal and genetic testing may be used as predictive factors for the additive effects of clonidine on the diuresis and natriuresis effects of diuretics in patients with cirrhosis with refractory ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
(35 reference statements)
0
24
0
1
Order By: Relevance
“…The T allele was also predictive of net sodium chloride and calcium excretion in response to loop diuretic use in healthy volunteers 42 . The rs5443 T allele may further predict response to clonidine in cirrhotics and healthy individuals 69,70 ; caution should be employed in interpreting these results as the studies were small and employed non-traditional endpoints.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…The T allele was also predictive of net sodium chloride and calcium excretion in response to loop diuretic use in healthy volunteers 42 . The rs5443 T allele may further predict response to clonidine in cirrhotics and healthy individuals 69,70 ; caution should be employed in interpreting these results as the studies were small and employed non-traditional endpoints.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…Indeed, clonidine improves the diuretic effects of spironolactone alone or the combination of furosemide and spironolactone in patients and experimental animal models with advanced liver cirrhosis and ascites [29][30][31]. Guanfacine, a distinct α 2 -adrenoceptor agonist, has approximately 60-fold more selectivity than clonidine for α 2A -adrenoceptors [32], which are located in the proximal tubular nephron in the inner stripe of the renal cortex [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for over 20 years that sympathetic dysregulation in cirrhotic patients leads to marked overactivity 2. With this in mind, the α 2 -adrenoceptor agonist, clonidine, should be considered, having recently been shown to significantly improve the 1-year survival when used in combination with diuretic therapy in a randomised study of 270 patients with refractory ascites 3. Importantly, this study also identified specific genotypes that predicted the degree of response to clonidine and diuretic combination therapy.…”
mentioning
confidence: 85%